Anesthetic management of an obstetric patient with idiopathic transverse myelitis: A unique approach! - Kirti N Saxena; Amrita Kaul; Mohammad Shakir (Wolters Kluwer Medknow Publications, 2019)
Transverse myelitis (TM) is a rare neurological disorder characterized by acute or subacute bilateral inflammation and myelin destruction in the spinal cord. A 14-year-old, primigravida with idiopathic TM presented to us with 38 weeks gestation for emergency cesarean section. There are potential anesthetic concerns with general anesthesia in the form of hyperkalemia following succinylcholine and delayed reversal from nondepolarizing muscle relaxants. Taking into consideration, the above-mentioned facts and level of sensory deficit of our patient; we successfully conducted the case under monitored anesthesia care with minimal analgesic support keeping our conventional anesthetic techniques as standby.